INOVASI ECO-GREEN CONCRETE, BETON EKONOMIS MUTU TINGGI DENGAN VARIASI KOMPOSISI AGREGAT DAUR ULANG SEBAGAI SUBSTITUSI AGREGAT KASAR - Rahma Nindya Ayu Hapsari; Haryadi, Bambang; Sutarto, Agung; Istianti, Monica Ayu; Panduwijaya, Joan Rafif; Lanjarsari, Aulia Putri (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2023)
The high level of infrastructure development at present forces old buildings to undergo repairs or even demolition to make way for new buildings that are more suitable and representative. The resulting demolition waste is usually discarded, becoming solid waste. The solution to the above problem is recycling the concrete waste as an alternative aggregate to replace some or all of the natural aggregates in the concrete mixture. Concrete with recycled aggregates is made with several composition variations of replacement to natural coarse aggregates, which is 0%, 25%, 35%, 45%, and 50%. The concrete will be tested for compressive strength at 28 days from the concrete mixture preparation. The research results showed that the highest compressive strength was found in the variation with a 25% replacement of natural coarse aggregates, which was 50.1 MPa, and the optimum compressive strength value is obtained at the variation of 23.51% recycled coarse aggregate substitution. Keywords: Recycled Aggregate; Innovation; Eco-Green Concrete; Concrete Compressive Strength; Sikament NN.